Human cerebral organoids: cellular composition and subcellular morphological features - Mateos-Martínez, Patricia; Coronel, Raquel; Sachse, Martin; González-Sastre, Rosa; Maeso, Laura; Rodriguez, Maria Josefa; Terrón, María C.; López-Alonso, Victoria; Liste, Isabel (Frontiers in Cellular Neuroscience, 2024)
Human cerebral organoids (hCOs) derived from pluripotent stem cells are very promising for the study of the neurodevelopment and in the investigation of healthy or diseased brain. To help establish hCOs as a powerful research model, it is desirable to deepen the morphological characterization of their cellular components.In this study, we have analyzed the cell types that compose hCOs of 45 days of culture by immunofluorescence and RT-qPCR assays. We have also analyzed the subcellular morphological characteristics by Transmission Electron Microscopy (TEM). Our results show the development of proliferative zones remarkably similar to those found in human brain development with cells having a polarized structure surrounding a central cavity with tight junctions and cilia. In addition, we describe the presence of immature and mature migrating neurons, astrocytes, as well as oligodendrocyte precursor cells and microglia-like cells. The ultrastructural characterization presented in this work provides valuable information on the structural development and morphology of the hCOs components and is of general interest for future research on the mechanisms that alter hCOs cell structure or function.